Skinner’s Methodology: A Weapon against Liberalism - Bustamante Kuschel, Gonzalo (Res Publica. Revista de Historia de las Ideas Políticas, 2018)
In this article, I suggest that it is plausible to argue that Skinner’s methodology is inseparable from his intention to retrieve republicanism. This makes itself evident in the way he structures his critique of John Rawls. In line with Hobbes, this British historian interprets Rawls’s A Theory of Justice as another example of theory being politically neutralized. I will present the main aspects of Skinner’s analysis of Rawlsian liberalism from a neo-Machiavellian perspective, and discuss to what degree this analysis is or is not conclusive vis-à-vis the relationship between Rawls and republicanism. Finally, I will assess to what extent it is ideology that motivates the British historian to put his methodology in line with republicanism.
Keywords: Skinner; Rawls; republicanism; Hobbes; Machiavelli